Hyperimmune bovine colostrum reduces gastrointestinal carriage of uropathogenic Escherichia coli - Sarah Larcombe; Melanie L. Hutton; Dena Lyras (Taylor & Francis Group, 2019)
Debilitating recurrent urinary tract infections (UTIs) are often associated with gastrointestinal colonisation by uropathogens, such as uropathogenic Escherichia coli (UPEC), suggesting that these populations might be a suitable target for the treatment and prevention of recurrent UTI. However, antimicrobial treatment is generally unable to prevent recurrent UTI, and often selects for multidrug resistant uropathogens in the gut, and causes dysbiosis of the gut, vaginal, and urinary microbiota. Of note, the globally-disseminated multi drug resistant UPEC lineage, ST131, is known to both persistently colonise the gut and the urinary tract, and is associated with antibiotic treatment failure, indicating the need for novel non-antibiotic therapeutics for the treatment of UTI. This study therefore presents hyperimmune bovine colostrum (HBC) as a suitable therapy for the treatment of UPEC gastrointestinal colonisation. This work demonstrates that the vaccination of pregnant cows with inactivated cells from a ST131 UPEC isolate results in a highly specific anti-UPEC HBC, and that this product is able to disrupt the gastrointestinal colonisation of ST131 UPEC in mice.